1995
DOI: 10.1002/1097-0142(19950415)75:8<2077::aid-cncr2820750808>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute-phase protein response and survival duration of patients with pancreatic cancer

Abstract: Background. Current methods to predict survival duration of patients with pancreatic cancer are limited. The aim of this study was to determine whether certain nutritional indices and the acute‐phase protein response are prognostic factors independent of disease stage for patients with unresectable pancreatic cancer. Methods. Variables at the time of diagnosis of 102 patients with unresectable pancreatic cancer were entered into a Cox's proportional hazards model. Included in the analysis were the serum concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
170
4
10

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(198 citation statements)
references
References 21 publications
9
170
4
10
Order By: Relevance
“…An APPR has been well documented among patients with cancer, including gastric and oesophageal malignancies, and an elevated serum CRP has been identified as an adverse prognostic indicator, independent of stage of disease, among these patients (Rashid et al, 1982;Falconer et al, 1995;Kodama et al, 1999;McMillan et al, 2001McMillan et al, , 2003Nozoe et al, 2001;Forrest et al, 2003). The present study has confirmed these findings.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…An APPR has been well documented among patients with cancer, including gastric and oesophageal malignancies, and an elevated serum CRP has been identified as an adverse prognostic indicator, independent of stage of disease, among these patients (Rashid et al, 1982;Falconer et al, 1995;Kodama et al, 1999;McMillan et al, 2001McMillan et al, , 2003Nozoe et al, 2001;Forrest et al, 2003). The present study has confirmed these findings.…”
Section: Discussionsupporting
confidence: 85%
“…Systemic inflammation has been found in association with the majority of advanced solid epithelial malignancies and at the time of diagnosis up to 50% of patients may have an elevated acute phase protein response (APPR) (Falconer et al, 1995). The presence of an APPR has been associated with weight loss, the presence of hypermetabolism and anorexia, extent of disease, the development of recurrence in advanced cancer, and adverse prognosis (independent of stage of disease) (Rashid et al, 1982;Kodama et al, 1999;McMillan et al, 2001McMillan et al, , 2003Nozoe et al, 2001;Forrest et al, 2003).…”
mentioning
confidence: 99%
“…The magnitude of the acute-phase protein response in patients with metastatic colorectal cancer correlated with reduced survival in the present study and in previous studies of patients with other tumours [31]. Patients and volunteers showed similar TNF production and cell concentrations, and neither variable correlated with the presence or magnitude of the acute-phase protein response, and failed to separate the diverse groups in terms of outcome.…”
Section: Discussioncontrasting
confidence: 48%
“…An elevated C-reactive protein concentration has previously been shown to have independent prognostic value in patients with unresectable pancreatic ductal adenocarcinoma (Falconer et al, 1995;Ueno et al, 2000;Engelken et al, 2003). However, to our knowledge the prognostic value of C-reactive protein has not been previously examined in patients with operable disease.…”
mentioning
confidence: 93%